Sperm Selection Using Microfluidic Techniques Significantly Decreases Sperm DNA Fragmentation (SDF), Enhancing Reproductive Outcomes: A Systematic Review and Meta-Analysis - Alma Gisbert Iranzo; Marina Cano-Extremera; Irene Hervás; Mar Falquet Guillem; María Gil Juliá; Ana Navarro-Gomezlechon; Rosa María Pacheco-Rendón; Nicolás Garrido (Biology, 2025)
This study aimed to compare sperm parameters and reproductive outcomes after sperm selection using microfluidic chips versus conventional techniques (swim-up/density gradients). A systematic review and meta-analysis were performed after the extraction of relevant data from thirty-nine studies that met the inclusion criteria. Mean difference or odds ratio was calculated for each outcome. The analysis revealed that sperm selection using microfluidics yields lower sperm DNA fragmentation (MD = −9.98 [−13.19, −6.76], p < 0.00001), increased progressive motility (MD = 14.50 [7.84, 21.71], p = 0.04), total motility (MD = 10.68 [6.04, 15.31], p < 0.00001) and morphology (MD = 1.41 [0.67, 2.16], p = 0.0002). Significant differences were also found in the fertilization rate/MII oocyte microinjected (OR = 1.22 [1.01, 1.46], p = 0.04), implantation rate/embryo transfer (ET) (OR = 4.51 [1.42, 14.37], p = 0.01), clinical pregnancy/ET (OR = 1.73 [1.22, 2.45], p = 0.002), ongoing pregnancy/ET (OR = 1.99 [1.03, 3.83], p = 0.04), live birth rate/first cycle (OR = 1.59 [1.12, 2.24], p = 0.009) and per all embryo transfer (OR = 1.65 [1.06, 2.55], p = 0.03). No significant differences were found in embryo euploidy/number of biopsied blastocysts (OR = 1.34 [0.88, 2.04], p = 0.77), biochemical pregnancy/ET (OR = 1.23 [0.84, 1.80], p = 0.29), miscarriage rate/cycle (OR = 0.84 [0.54, 1.31], p = 0.35) and per pregnancy (OR = 0.71 [0.50, 1.02], p = 0.07), live birth rate/first embryo transfer (OR = 1.60 [0.80, 3.22], p = 0.18) and per concluded cycle (OR = 1.03 [0.53, 2.00], p = 0.92). To summarize, microfluidics may offer a beneficial approach in certain situations, particularly for patients with elevated sperm DNA fragmentation (SDF) levels. However, its integration into routine clinical practice cannot be justified yet in terms of cost-effectiveness. Additional research is needed to provide more comprehensive data on reproductive outcomes, especially live birth rates, which remain the ultimate goal of assisted reproductive technologies.